الوقف النقدي وتعبئة مصادر تمويل المشروعات الوقفية دراسة حالة بعض البلدان الإسلامية وآفاق تطبيقها في الجزائر - قابوسة, علي; وصيف خالد, إبراهيم; عبيد, حياة (جامعة الوادي - University of Eloued, 2020)
ملخص: تبحث دراستنا في موضوع الأوقاف النقدية ودورها في تعبئة مصادر تمويل المشروعات الخيرية الوقفية؛ إن الوقف النقدي المبني على حبس النقود وتسبيل منفعتها واستثمار أرباحها فيما يعود بالنفع على الفرد والمجتمع. يشكل الأساس المادي للخدمات الاجتماعية والمنافع العامة، وتمويل شبكة واسعة من المؤسسات والمشروعات والأنشطة الخدمية. ومن خلال تتبع التجارب العالمية للأوقاف النقدية فإن هناك آليات ونماذج لوقف النقود في كل من ماليزيا وتركيا والكويت والهند؛ وكذا تجارب مؤسسات دولية؛ وأهم النماذج المعتمدة في وقف النقود هي نموذج أسهم الوقف ونموذج الوقف النقدي عن طريق الهاتف الخلوي ونموذج الوقف النقدي التعاوني؛ وبعد تحليل ونقد هذه النماذج؛ فإن واقع الأوقاف في الجزائر وآفاق إمكانية تطبيق الوقف النقدي يتطلب إرادة حكومية جادة مدعومة بتشريعات سياسية تمكّن من اعتماده كآلية للتمويل، كما يتوجب نشر الوعي بين أفراد المجتمع بأهمية هذا النوع من الأوقاف وتبيين الأثر الإيجابي لنتائجه. Abstract: Our study examines the subject of monetary endowments and their role in mobilizing funding sources for endowment charitable projects. The monetary endowment is based on the confinement of money and the expense of its benefit and investment of its profits in the interests of the individual and society. It forms the material basis for social services and public goods, and financing an extensive network of institutions, projects, and service activities. Through tracking the global experiences of monetary endowments, there are mechanisms and models for stopping money in each of Malaysia, Turkey, Kuwait and India; as well as the experiences of international institutions; Criticism of these models; the reality of endowments in Algeria and the prospects for the implementation of the monetary endowment require serious government will backed by political legislation that enables its adoption as a financing mechanism, and awareness must be spread among members of society of the importance of this type of endowment and the positive impact of its results.
The Monetary Endowment and the Mobilization of Funding Sources for Endowment Projects. A Case Study of Some Islamic Countries and the Prospects for their Application in Algeria
Keywords: التمويل ; مصادر إيرادات أخرى ; المشروعات التعاونية; Funding ; Other sources of revenue ; Collaborative projects